Comparative Analysis of Efficient Market for Sharia and Conventional Stocks in ASEAN countries - Ahmad Rodoni; Haikal Djauhari; Yusro Rahma; Alhussaini Alawad Alhassan (Faculty of Shariah and Law, UIN Syarif Hidayatullah Jakarta, 2022)
This study analyzes and compares the weak forms of Islamic and conventional stock market efficiency in ASEAN countries. The data were taken from BEI Syariah (JKISSI), Jakarta Stock Exchange (JKSE), FTSE Bursa Malaysia EMAS Syariah (FTFBMS), FTSE Malaysia KLCI (KLSE), SET Index (SETI), and FTSE SET Syariah (FTFSTSH) from January 2015 to August 2021. To avoid analytical bias due to the COVID-19 Pandemic, the data is divided into two periods, January 2015 to December 2019 and January 2020 to August 2021. The contribution of this research is to compare the market efficiency of the weak form of Islamic and conventional stocks over two periods with different methods, namely Variance Ratio Test, Run Test, ARIMA Model, and Recurrent Neural Network (RNN). This study shows that Islamic stocks in these countries are more efficient from January 2015 to December 2019. On the other hand, conventional stocks are more efficient from January 2020 to August 2021 (during the COVID-19 Pandemic). Abstrak Penelitian ini menganalisa dan membandingkan bentuk lemah dari efisiensi pasar saham syariah dan konvensional di negara-negara ASEAN. Data berasal dari BEI Syariah (JKISSI), Bursa Efek Jakarta (JKSE), FTSE Bursa Malaysia EMAS Syariah (FTFBMS), FTSE Malaysia KLCI (KLSE), SET Index (SETI), dan FTSE SET Syariah (FTFSTSH) dari Januari 2015 hingga Agustus 2021. Untuk menghindari bias analisa akibat pandemi COVID-19, data dibagi menjadi dua periode, Januari 2015 hingga Desember 2019 dan Januari 2020 hingga Agustus 2021. Penelitian ini membandingkan bentuk lemah dari efisiensi pasar saham syariah dan konvensional selama dua periode waktu dengan metode berbeda, yaitu Variance Ratio Test, Run Test, Model ARIMA, dan Recurrent Neural Network (RNN). Studi menunjukkan bahwa Saham Syariah di negara-negara tersebut lebih efisien pada periode Januari 2015 hingga Desember 2019. Di sisi lain, saham konvensional lebih efisien pada periode Januari 2020 hingga Agustus 2021 (selama pandemi COVID-19).